Pengembangan Media Pembelajaran Pop Up Book Tema 9 Menjelajah Luar Angkasa Kelas VI Sekolah Dasar - Putri, Anggi Juliana; Junaidi, Ilham Arvan; Syaflin, Sylvia Lara (Indonesian Research Journal on Education, 2022)
This study aims to (1) find out how to develop pop up book learning media into learning media onvalid science material, (2) find out how to develop pop up book learning media into learning media on practical science material. The needs analysis in this study is the lack of use of learning media in science material, teachers only use textbooks and picture posters. This research method is development (Research and Deveploment) using the ADDIE model. The methods used in datacollection are interviews, documents, questionnaires. The results of this study indicate that the pop up book learning media developed in this study is categorized as very valid. In this study, the validity value obtained from the three validation results of learning media, science learning materials, and language scores obtained sequentially are 100%, 87.5%, 77.5%. Furthermore, the pop up book learning media developed was declared very practical, obtaining a practicality score of 92.8%. It can be concluded that the pop up book learning media for the solar system can be used for learning media for elementary school students.